Clinical significance of the neutrophil-to-lymphocyte ratio and platelet-to-lymphocyte ratio in acute exacerbations of COPD: present and future. (2nd November 2022) - Zinellu, Angelo; Zinellu, Elisabetta; Mangoni, Arduino A.; Pau, Maria Carmina; Carru, Ciriaco; Pirina, Pietro; Fois, Alessandro G.
Acute exacerbations of chronic obstructive pulmonary disease (AECOPD) are a leading cause of hospitalisation and death in COPD patients. In addition to the identification of better strategies to prevent AECOPD, there is an intense focus on discovering novel markers of disease severity that enhance risk stratification on hospital admission for the targeted institution of aggressive versus supportive treatments. In the quest for such biomarkers, an increasing body of evidence suggests that specific indexes derived from routine complete blood counts, i.e. the neutrophil-to-lymphocyte ratio (NLR) and the platelet-to-lymphocyte ratio (PLR), can significantly predict adverse outcomes in AECOPD. This narrative review discusses the current evidence regarding the association between the NLR and the PLR on admission and several clinical end-points (need for invasive ventilation, noninvasive mechanical ventilation failure, admission to an intensive care unit, pulmonary hypertension, length of hospitalisation, and mortality) in AECOPD. Future research directions and potential clinical applications of these haematological indexes in this patient group are also discussed. A review of the relationship between neutrophil-to-lymphocyte (NLR) and platelet-to-lymphocyte (PLR) ratios and several adverse outcomes in AECOPD. NLR emerges as a useful predictor of mortality in these patients; the prognostic value of PLR is less clear. https://bit.ly/3Jo6XGs